KINERJA KEUANGAN PERBANKAN DAN RETURN SAHAM: PERAN RASIO KECUKUPAN MODAL SEBAGAI VARIABEL MODERASI - Meliza, Meliza; Herlinah, Herlinah; Magetana, Dewi Yuniar (LPPM Universitas Malikussaleh, 2025)
The banking sector is a key foundation of the Indonesian economic system. The stability and contribution of this sector are significantly influenced by bank financial performance and the dynamics of banking stocks in the capital market. Based on this, this study aims to investigate the effect of banking financial performance, as measured by the loan-to-deposit ratio (LDR) and return on assets (ROA), on stock returns. This study also includes the capital adequacy ratio (CAR) as a moderating variable to assess whether CAR strengthens or weakens the relationship between LDR and ROA on stock returns. The research sample consists of banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. The analytical method used is multiple regression with the Ordinary Least Square (OLS) approach. The analysis results show that ROA has a positive and significant effect on stock returns, with a t-statistic of 2.00, which is significant at the 5% level. Furthermore, CAR is proven to moderate the relationship between ROA and stock returns, indicated by a t-statistic of -1.9, which is also significant at the 5% level. In contrast, LDR did not show a significant effect on stock returns, and CAR failed to moderate the relationship between LDR and stock returns.